(untitled) (REMUNOM, 2023)
Myelomeningocele is a pathology in which the neural tube of the developing fetus does not have an adequate closure, causing nerve damage due to exposure of the medulla, meninges, cerebrospinal fluid and/or nerve roots that develop without protection in the posterior region of the fetus. , can generate alterations of different degrees, varying with the amount of nerve tissue exposed and the level of involvement. This study is a review that aims to understand the physiotherapeutic approaches in the treatment of children with myelomeningocele, the above was formulated based on articles taken from the PEDro, SciELO, PubMed and Google Scholar databases, written in Portuguese, Spanish or English. Articles whose methodology was not well described or whose results were inconclusive were excluded. At the end of this research, it can be pointed out that physiotherapy plays a fundamental role in the functional development of patients with myelomeningocele, being essential for different types of injuries, potentially increasing the chances of the child achieving postural balance and even walking.